Intuitive thinking predicts false memory formation due to a decrease in inhibitory efficiency - Gronchi, Giorgio; Righi, Stefania; Gavazzi, Gioele; Giganti, Fiorenza; Viggiano, Maria Pia (Frontiers in Psychology, 2023)
False memory formation is usually studied using the Deese-Roediger-McDermott paradigm (DRM), in which individuals incorrectly remember words that were not originally presented. In this paper, we systematically investigated how two modes of thinking (analytical vs. intuitive) can influence the tendency to create false memories. The increased propensity of intuitive thinkers to generate more false memories can be explained by one or both of the following hypotheses: a decrease in the inhibition of the lure words that come to mind, or an increased reliance on the familiarity heuristic to determine if the word has been previously studied. In two studies, we conducted tests of both recognition and recall using the DRM paradigm. Our observations indicate that a decrease in inhibitory efficiency plays a larger role in false memory formation compared to the use of the familiarity heuristic.